ECOLOGICAL FACTORS INFLUENCING THE RELATIONSHIPS BETWEEN KLEBSIELLA AND SHIGELLA IN MIXED CULTURE - Hentges, David J. (1964)
Hentges, David J. (Loyola University, Chicago, Ill.), and MacDonald Fulton. Ecological factors influencing the relationships between Klebsiella and Shigella in mixed cultures. J. Bacteriol. 87:527–535. 1964.—Viable-cell counts of Shigella flexneri and Klebsiella (Aerobacter aerogenes) in pure and mixed culture were made during growth under predetermined conditions of temperature, pH, oxygen supply, and nutrient supply. In pure culture, environmental changes had marked effects on the Shigella populations. Klebsiella populations were not affected except at 44 C or when aerated; under these conditions, the populations were smaller. In nonaerated mixed culture, under different conditions of temperature, pH, and nutrient supply, Klebsiella interfered with the multiplication of Shigella. Exponential growth of Shigella was interrupted at about the time Klebsiella populations attained a maximal size. In contrast, the presence of Klebsiella in an aerated mixture had little or no effect on Shigella multiplication because Klebsiella failed to attain a maximal population. Different environmental conditions resulted in different Klebsiella to Shigella ratios in mixed cultures. When conditions were favorable for Shigella multiplication, as shown by pure culture controls, the proportion of Shigella in the mixture was generally greater than when conditions were unfavorable.